Alat-Alat Kerja Tukang Meja Kayu Memajukan Usaha Keluarga Di Padang Bulan Medan - Siregar, Delisma; Sitanggang, Ernie SY; Bangun, Positron; Budianto, Gallio (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2022)
The current condition of the COVID-19 pandemic has made the economy mostly experience a setback, also experienced by partners, namely the Mulyadi family in Padang Buan, Medan City, not far from the Medan State Polytechnic. Mulayadi, who owns a grocery business selling basic necessities, was forced to close the business because of the declining number of buyers, including due to competition between the same businesses. Next the partners think what to do then turn around and start the table carpenter business. With conventional tools such as hand planers, hand saws, manual chisels and manual painting, partners make wooden tables, and sell them quickly to coffee shops in Padang Bulan around USU. With the help of his son, he tried to offer his wooden table through social media and it turned out that there was a request from the community. As demand from buyers increases, partners find it difficult to meet buyers and are constrained by increasing their business in making wooden tables because they require modern equipment such as electric planers, electric saws, electric drills, compressors, and painting gun units, and partners do not have the money to buy tools. the tool. This was conveyed to the Polmed lecturer to ask for help providing these tools. Then the implementation team carries out a survey, evaluating needs that can improve the work of partners, so that the implementation team of this service aims to help provide carpentry tools and provide training on the use of tools properly and safely. Then the service implementation team made a submission to Polmed through P3M and carried out a service program by handing over tools or machines in the form of 2 electric planers, 1 electric saw, 1 electric drill, compressor and painting gun unit. At the time of delivery, partners said that with manual equipment made of wooden tables as many as 1-2 tables per week, then with the availability of tools provided by Polmed through the chief executive, they could make 4-5 tables per week with more aesthetic ones, and therefore partners' opinions became increase.